2002
DOI: 10.2118/75455-pa
|View full text |Cite
|
Sign up to set email alerts
|

New View on Continuous-Removal Liquids From Gas Wells

Abstract: Summary The paper adopts the view that the liquid droplets entrained in gas wells tend to be flat and deduces new formulas for the continuous removal of liquids from gas wells. The results calculated from the formulas are smaller than those of Turner et al. However, the predicted results are in accord with the practical production performance of China's gas wells with liquids. The paper also gives the simple forms of these formulas and shows the load-up and near load-up production performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 3 publications
0
45
1
Order By: Relevance
“…As presented in Table 1, several investigators have suggested different modified expressions derived from Turner model. Turner et al, 1969 Created the widely accepted Turner equation Coleman et al, 1991 Suggested not to use the 20% correction factor for low pressure gas wells Nosseir et al, 2000 Considered influences from different flow regimes Li et al, 2002 Involved the droplets' shape Veeken et al, 2003 Defined the concept of Turner ratio Guo et al, 2006 Took the minimum required kinetic energy of gas flow into account Belfroid et al, 2008 Concerned with the effects due to wellbore inclination Sutton et al, 2010 Used more realistic PVT properties Zhou and Yuan, 2010 Included the liquid droplet concentration in gas wells Veeken et al, 2010 Designed a specific expression for offshore gas wells Luan and He, 2012 Comprised droplets rollover in the gas rising process…”
Section: Current Prediction Approachesmentioning
confidence: 99%
“…As presented in Table 1, several investigators have suggested different modified expressions derived from Turner model. Turner et al, 1969 Created the widely accepted Turner equation Coleman et al, 1991 Suggested not to use the 20% correction factor for low pressure gas wells Nosseir et al, 2000 Considered influences from different flow regimes Li et al, 2002 Involved the droplets' shape Veeken et al, 2003 Defined the concept of Turner ratio Guo et al, 2006 Took the minimum required kinetic energy of gas flow into account Belfroid et al, 2008 Concerned with the effects due to wellbore inclination Sutton et al, 2010 Used more realistic PVT properties Zhou and Yuan, 2010 Included the liquid droplet concentration in gas wells Veeken et al, 2010 Designed a specific expression for offshore gas wells Luan and He, 2012 Comprised droplets rollover in the gas rising process…”
Section: Current Prediction Approachesmentioning
confidence: 99%
“…Through the experimental data, liquid flow rate and critical gas flow rate of three main models (Turner model [1], Colemon model [2,3] and LiMin model [4]) in the tube are calculated, drawing the following correlation curves shown in Fig. (1).…”
Section: Applicable Model Experiments For Crit-ical Gas Flow Rate Of mentioning
confidence: 99%
“…They concluded that the Turner model is suitable for wellhead pressure less than 3.45 MPa and that the 20% upward adjustment is not necessary to calculate the critical gas velocity. Li et al [9] assumed that droplets in gas wells are elliptical and derived a new formula for calculating the critical liquid-carrying gas velocity, whose result was only 1/3 of the result calculated by the Turner model. Later, many scholars have made various changes to the Turner model and the Li model [9], but they are only suitable for the vertical well and laminar flow.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [9] assumed that droplets in gas wells are elliptical and derived a new formula for calculating the critical liquid-carrying gas velocity, whose result was only 1/3 of the result calculated by the Turner model. Later, many scholars have made various changes to the Turner model and the Li model [9], but they are only suitable for the vertical well and laminar flow. Based on the previous study [6][7][8], Nosseir et al [10] considered the influence of flow regime on the calculation result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation